Unruptured intracranial aneurysms: development, rupture and preventive management - Etminan, Nima; Rinkel, Gabriel J. E. (Nature reviews. Neurology, 2016)
Saccular unruptured intracranial aneurysms (UIAs) have a prevalence of 3% in the adult population, and are being increasingly detected because of improved quality and higher frequency of cranial imaging. Large amounts of data, providing varying levels of evidence, have been published on aneurysm development, progression and rupture, but less information is available on the risks and efficacy of preventive treatment. When deciding how to best manage UIAs, clinicians must consider the age and life expectancy of the patient, the estimated risk of rupture, the risk of complications attributed to preventive treatment, and the level of anxiety caused by the awareness of having an aneurysm. This Review highlights the latest human data on the formation, progression and rupture of intracranial aneurysms, as well as risks associated with preventive treatment. Considering these we discuss the implication for clinical management. Furthermore, we highlight pivotal questions arising from current data on intracranial aneurysms and the implications the data have for future experimental or clinical research. We also discuss data on novel radiological surrogates for rupture for those aneurysms that do not require preventive occlusion. Finally, we provide guidance for clinicians who are confronted with patients with incidentally detected UIAs.
Gesehen am 28.02.2019